2019
DOI: 10.15252/embr.201847381
|View full text |Cite
|
Sign up to set email alerts
|

The multi PAM 2 protein Upa2 functions as novel core component of endosomal mRNA transport

Abstract: mRNA transport determines spatiotemporal protein expression. Transport units are higher‐order ribonucleoprotein complexes containing cargo mRNAs, RNA‐binding proteins and accessory proteins. Endosomal mRNA transport in fungal hyphae belongs to the best‐studied translocation mechanisms. Although several factors are known, additional core components are missing. Here, we describe the 232 kDa protein Upa2 containing multiple PAM2 motifs (poly[A]‐binding protein [Pab1]‐associated motif 2) as a novel core component… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…Intriguingly, we also identified numerous potential RNA-binding proteins as targets of STRIPAK, thus suggesting extensive regulation of spatio-temporal gene expression by STRIPAK at the posttranscriptional level. Among the candidates were Pab1 (SMAC_03445), a poly(A)-binding protein that shuttles on endosomes [56], as well as GUL1, a regulator of fungal morphogenesis [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, we also identified numerous potential RNA-binding proteins as targets of STRIPAK, thus suggesting extensive regulation of spatio-temporal gene expression by STRIPAK at the posttranscriptional level. Among the candidates were Pab1 (SMAC_03445), a poly(A)-binding protein that shuttles on endosomes [56], as well as GUL1, a regulator of fungal morphogenesis [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…septins for endosomal assembly [60][61][62]. Transport mRNPs are stabilized by the scaffold protein Upa2 and linked to endosomes via the FYVE domain protein Upa1 [51,56]. A phylogenetic analysis revealed that important core components of endosomal transport like Upa2 and the key RBP Rrm4 are missing in ascomycetes [52].…”
Section: Gul1 Is Trafficking On Endosomesmentioning
confidence: 99%
“…In this case, mRNA transport seems to drive not only asymmetric localisation of mRNAs to support site-specific protein synthesis, but may also play additional roles, such as enabling the efficient assembly of protein complexes in situ. Such [116]. b Endosomal/lysosomal hitchhiking in neurons.…”
Section: Mrna Hitchhiking In Filamentous Fungimentioning
confidence: 99%
“…Its deletion causes a 50% reduction in the number of processively-moving mRNAs and causes defects in hyphal growth. This protein is thought to act as a scaffold stabilising the RNA granule complex during transport [ 116 ].
Fig.
…”
Section: Hitchhiking Onto Endosomes As a Mechanism Of Transportmentioning
confidence: 99%
See 1 more Smart Citation